EMPLOYEE ENGAGEMENT DOSEN DI UNIVERSITAS JAMBI: EMPLOYEE ENGAGEMENT OF JAMBI UNIVERSITY’S LECTURERS - Fadzlul, Semi (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2018)
INTRODUCTION One of the causes of the decline in the quality of lecturers is because lecturers are busy working outside the campus, and looking for projects in accordance with their fields of expertise. For this reason, it is important to describe how employee engagement, which is an emotionally and intellectually positive attitude of an employee who are fully aware of his attachment to his work or duties and are loyal and committed to the institution for which he works. METHOD This study uses a quantitative method through cross-sectional approach through a survey method which aims to determine the description of Employee Engagement of Jambi University’s Lecturers. The research population was 102 lecturers of Jambi University consisting of 11 Faculties, with inclusion criteria of permanent lecturers and non PNS lecturers (contract lecturers). The technique used is Purposive sampling. The data collection tool is the scale of Employee Engagement. The study was conducted from February to August 2018 at Jambi University. The analysis used is regression analysis and variance analysis. RESULTS This study concludes that employee engagement compared between age groups, years of service, academic positions, ethnicity, and marital status is the same. CONCLUSIONS AND RECOMMENDATIONS There are no differences in employee engagement based on the above categories. More specifically, there is no difference in employee engagement between males and females. Employee engagement is also equal based on the last education category where there is no difference between master and PhD graduates. Likewise, there is also no difference in employee engagement between Civil Servants (PNS) lecturers and Non PNS lecturers. Kata Kunci: Employee engangement, UNJA